Stain-resistant high-hardness coating and application thereof
By using nano -modified titanium silicon aluminum powder, organic silicon emulsion and wax emulsion in the inner wall coatings, combined with other mineral powder and negative ion additives, the problem of low hardness and poor stain removal performance of existing coatings have been solved. Coatings with high hardness and excellent pollution resistance.
Patent Information
- Application Number
- CN202411697430.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-01-24
AI Technical Summary
The existing interior wall coatings have low hardness, are prone to damage, and have poor stain removal performance, making it difficult to meet the needs of stain resistance and high hardness.
It is composed of nano-modified titanium silicon aluminum powder, silicone emulsion and wax emulsion, combined with titanium dioxide, heavy calcium carbonate, wollastonite powder, mica powder, nano-titanium phosphate, diatomaceous earth and negative ion additives to form high hardness and coatings with excellent stain resistance.
The high hardness (more than 2H) and high stain removal rate of coatings and paint films have been realized. The removal capacity of a variety of stains has reached 10 levels, which significantly improves the dirt resistance of the coating.
Smart Images

Figure BDA0005153494620000091 
Figure BDA0005153494620000101 
Figure BDA0005153494620000102
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coatings, and in particular relates to a stain-resistant high-hardness coating and an application thereof. Background Art
[0002] As a decorative material, interior wall paint can not only beautify the interior space, but also protect the walls, prevent them from getting damp, block direct contact between the walls and smoke and dust, reduce wall aging, and at the same time play a certain role in purifying the air.
[0003] As people, especially children, move around indoors, walls are inevitably stained, graffitied and bumped, thus damaging interior wall paint. Existing interior wall paints are mainly composed of silicone emulsion, diatomaceous earth, calcium carbonate and additives (wetting agent, defoamer, dispersant, etc.). However, the paints in the prior art have low hardness, are easily damaged by collisions, and have poor stain removal performance (fouling resistance).
[0004] Therefore, there is an urgent need for a coating with stain resistance and high hardness. Summary of the invention
[0005] The purpose of the present invention is to provide a stain-resistant high-hardness coating and its application. The paint film formed by the coating provided by the present invention has high hardness and excellent stain-resistant performance.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The invention provides a stain-resistant high-hardness coating, which comprises the following components by mass percentage: 0.4-1.5% of dispersant, 0.02-0.5% of wetting agent, 0.1-0.55% of hydroxyethyl cellulose, 0.1-0.5% of defoaming agent, 0.02-0.4% of pH value regulator, 0.2-3% of film-forming aid, 5-30% of titanium dioxide, 0.2-2% of nano-modified titanium silicon aluminum powder, 3% of heavy calcium carbonate ...1-0.5% of pH value regulator, 0.02-0.4% of pH value regulator, 0.2-3% of film-forming aid, 0.1-0.5% of defoaming agent, 0.1-0.5% of defoaming agent, 0.02-0.4% of pH value regulator, 0.2-3% of film-forming aid, 0.1-0.5% of defoaming agent, 0.1-0.5% of defoaming agent, 0.02-0.4% of pH value regulator, 0.2-3% of film-forming aid, 0.1-0.5% of defoaming agent, 0.1-0.5% of defoaming agent, 0.1-0.5% of defoaming agent, 0.1-0.5% of defoaming agent, 0.1-0.5% of defoaming agent, 0.1-0.5% of defoaming agent, 0.1-0.5% of de ~30%, wollastonite powder 2~10%, mica powder 0.5~3%, nano titanium phosphate 0.2~2.5%, diatomaceous earth 1~5%, negative ion additive 0.2~2%, anti-scratch additive 0.1~0.85%, silicone emulsion 20~50%, wax emulsion 0.2~2%, preservative 0.1~1%, film-forming aid 0.5~4%, leveling agent 0.1~1%, thickener 0.1~1% and the balance water.
[0008] Preferably, the dispersant includes a sodium salt dispersant and an ammonium salt dispersant.
[0009] Preferably, the mass ratio of the sodium salt dispersant to the ammonium salt dispersant is (0.4-5):1.
[0010] Preferably, the pH adjuster includes at least one of organic ammonia and AMP-95; the pH value of the stain-resistant high-hardness coating is 8-9.
[0011] Preferably, the film-forming aid includes at least one of propylene glycol, ethylene glycol and ethylene glycol butyl ether.
[0012] Preferably, the titanium dioxide is rutile titanium dioxide.
[0013] Preferably, the negative ion additive includes at least one of tourmaline, ice stone and medical stone.
[0014] Preferably, the film-forming aid includes at least one of OE300 and TEXANOL.
[0015] Preferably, the defoaming agent includes at least one of a mineral oil defoaming agent, a silicone defoaming agent and a non-silicon defoaming agent.
[0016] The present invention also provides the use of the stain-resistant high-hardness coating described in the above technical solution in interior walls.
[0017] The invention provides a stain-resistant high-hardness coating, which comprises the following components by mass percentage: 0.4-1.5% of dispersant, 0.02-0.5% of wetting agent, 0.1-0.55% of hydroxyethyl cellulose, 0.1-0.5% of defoaming agent, 0.02-0.4% of pH value regulator, 0.2-3% of film-forming aid, 5-30% of titanium dioxide, 0.2-2% of nano-modified titanium silicon aluminum powder, 3% of heavy calcium carbonate ...1-0.5% of pH value regulator, 0.02-0.4% of pH value regulator, 0.2-3% of film-forming aid, 0.1-0.5% of defoaming agent, 0.1-0.5% of defoaming agent, 0.02-0.4% of pH value regulator, 0.2-3% of film-forming aid, 0.1-0.5% of defoaming agent, 0.1-0.5% of defoaming agent, 0.02-0.4% of pH value regulator, 0.2-3% of film-forming aid, 0.1-0.5% of defoaming agent, 0.1-0.5% of defoaming agent, 0.1-0.5% of defoaming agent, 0.1-0.5% of defoaming agent, 0.1-0.5% of defoaming agent, 0.1-0.5% of defoaming agent, 0.1-0.5% of de ~30%, wollastonite powder 2~10%, mica powder 0.5~3%, nano titanium phosphate 0.2~2.5%, diatomite 1~5%, negative ion additive 0.2~2%, anti-scratch additive 0.1~0.85%, organosilicon emulsion 20~50%, wax emulsion 0.2~2%, preservative 0.1~1%, film-forming additive 0.5~4%, leveling agent 0.1~1%, thickener 0.1~1% and the balance of water. Nano-modified titanium silicon aluminum powder is added to the coating of the present invention, and the nano-modified titanium silicon aluminum powder cooperates with the organosilicon emulsion, wax emulsion, wollastonite powder, mica powder and additives to improve the covering power and hardness of the coating; the organosilicon emulsion and wax emulsion are compounded to make the coating have super strong stain resistance and graffiti resistance, and extremely high stain removal rate. The results of the embodiments show that the paint film formed by the coating provided by the present invention has a hardness of more than 2H, and the removal ability of six types of stains, namely, edible vinegar, black tea, blue-black ink, water-soluble melanin, alcohol-soluble melanin, vaseline and carbon black mixture, is level 10. DETAILED DESCRIPTION
[0018] The invention provides a stain-resistant high-hardness coating, which comprises the following components by mass percentage: 0.4-1.5% of dispersant, 0.02-0.5% of wetting agent, 0.1-0.55% of hydroxyethyl cellulose, 0.1-0.5% of defoaming agent, 0.02-0.4% of pH value regulator, 0.2-3% of film-forming aid, 5-30% of titanium dioxide, 0.2-2% of nano-modified titanium silicon aluminum powder, 3% of heavy calcium carbonate ...1-0.5% of pH value regulator, 0.02-0.4% of pH value regulator, 0.2-3% of film-forming aid, 0.1-0.5% of defoaming agent, 0.1-0.5% of defoaming agent, 0.02-0.4% of pH value regulator, 0.2-3% of film-forming aid, 0.1-0.5% of defoaming agent, 0.1-0.5% of defoaming agent, 0.02-0.4% of pH value regulator, 0.2-3% of film-forming aid, 0.1-0.5% of defoaming agent, 0.1-0.5% of defoaming agent, 0.1-0.5% of defoaming agent, 0.1-0.5% of defoaming agent, 0.1-0.5% of defoaming agent, 0.1-0.5% of defoaming agent, 0.1-0.5% of de ~30%, wollastonite powder 2~10%, mica powder 0.5~3%, nano titanium phosphate 0.2~2.5%, diatomaceous earth 1~5%, negative ion additive 0.2~2%, anti-scratch additive 0.1~0.85%, silicone emulsion 20~50%, wax emulsion 0.2~2%, preservative 0.1~1%, film-forming aid 0.5~4%, leveling agent 0.1~1%, thickener 0.1~1% and the balance water.
[0019] The stain-resistant high-hardness coating provided by the present invention includes 0.4-1.5% of dispersant by mass percentage. In the embodiment of the present invention, the dispersant may be specifically 0.5%, 0.8%, 1.0%, 1.2% or 1.5%.
[0020] In the present invention, the dispersant preferably includes a sodium salt dispersant and an ammonium salt dispersant; the mass ratio of the sodium salt dispersant to the ammonium salt dispersant is preferably (0.4-5):1. As an embodiment, the mass ratio of the sodium salt dispersant to the ammonium salt dispersant can be (0.5-4):1, or (0.6-2):1. The present invention uses a sodium salt dispersant and an ammonium salt dispersant as a composite dispersant, which can further improve the dispersibility of each component in the coating.
[0021] The present invention has no particular limitation on the sources of the sodium salt dispersant and the ammonium salt dispersant, and commercially available products known to those skilled in the art can be used. In an embodiment of the present invention, the sodium salt dispersant is sodium salt dispersant SN-5040 (polyphenylene acid sodium salt), produced by San Nopco, Japan; and the ammonium salt dispersant is ammonium salt dispersant SN-5027, produced by San Nopco, Japan.
[0022] The stain-resistant high-hardness coating provided by the present invention includes 0.02-0.5% of wetting agent, preferably 0.1-0.5% by mass percentage. The present invention limits the amount of wetting agent to the above range, which can further improve the dispersibility of each component.
[0023] The present invention has no special limitation on the source of the wetting agent, and commercially available products known to those skilled in the art can be used. In an embodiment of the present invention, the wetting agent is wetting agent PE-100.
[0024] The stain-resistant high-hardness coating provided by the present invention includes 0.1-0.55% hydroxyethyl cellulose by mass percentage. In an embodiment of the present invention, the hydroxyethyl cellulose may be specifically 0.1%, 0.2%, 0.3%, 0.4% or 0.5%. In the present invention, the hydroxyethyl cellulose has multiple functions such as thickening, suspension, dispersion, film formation, and water retention, thereby improving the comprehensive performance of the coating. The present invention limits the amount of hydroxyethyl cellulose to the above range, which can further improve the comprehensive performance of the coating.
[0025] The present invention has no particular limitation on the source of the hydroxyethyl cellulose, and commercial products known to those skilled in the art can be used. In an embodiment of the present invention, the hydroxyethyl cellulose is 250HBR, nonionic cellulose ether, Ashland.
[0026] The stain-resistant high-hardness coating provided by the present invention includes 0.1-0.5% defoamer, preferably 0.2-0.5% by mass percentage. The present invention limits the amount of defoamer to the above range, which can fully remove bubbles in the coating and avoid holes in the paint film.
[0027] In the present invention, the defoamer preferably includes at least one of a mineral oil defoamer, a silicone defoamer and a non-silicon defoamer.
[0028] The present invention has no special limitation on the source of the defoamer, and commercial products known to those skilled in the art can be used. In an embodiment of the present invention, the defoamer is a mineral oil defoamer NXZ, BASF.
[0029] The stain-resistant high-hardness coating provided by the present invention includes 0.02-0.4% of a pH regulator, preferably 0.1-0.4%, and more preferably 0.2-0.4%, by mass percentage. The present invention limits the amount of the pH regulator to the above range, so that the coating has a suitable pH value, which is more conducive to improving the stability and adhesion of the coating.
[0030] In the present invention, the pH adjuster preferably includes at least one of organic ammonia and AMP-95.
[0031] The present invention has no particular limitation on the source of the pH adjuster, and commercially available products known to those skilled in the art may be used.
[0032] The stain-resistant high-hardness coating provided by the present invention includes 0.2-3%, preferably 0.5-3%, and more preferably 1-3% of a film-forming aid in terms of mass percentage. In the present invention, the film-forming aid can promote film formation, improve construction performance, and improve the quality and use effect of the coating. The present invention limits the amount of the film-forming aid to the above range, which can further improve the quality and use effect of the coating.
[0033] In the present invention, the film-forming aid preferably includes at least one of propylene glycol, ethylene glycol and ethylene glycol butyl ether, and more preferably propylene glycol. The present invention uses propylene glycol as a film-forming aid, which is more environmentally friendly and has low odor compared to ethylene glycol, and can improve the antifreeze property of the coating.
[0034] The present invention has no particular limitation on the source of the film-forming aid, and commercially available products known to those skilled in the art may be used.
[0035] The stain-resistant high-hardness coating provided by the present invention includes 5-30% titanium dioxide, preferably 10-30%, and more preferably 20-30% by mass percentage. In the present invention, the titanium dioxide is preferably rutile titanium dioxide. The present invention adds rutile titanium dioxide as a white pigment to improve the dry and wet hiding power of the paint film, so that the coating has excellent weather resistance and yellowing resistance. The present invention limits the amount of titanium dioxide to the above range, which can further improve the performance of the coating.
[0036] The present invention has no particular limitation on the source of the titanium dioxide, and commercially available products known to those skilled in the art may be used.
[0037] The stain-resistant high-hardness coating provided by the present invention comprises 0.2-2%, preferably 0.5-2%, and more preferably 1-2% of nano-modified titanium-silicon-aluminum powder by mass percentage. The present invention adds nano-modified titanium-silicon-aluminum powder, which cooperates with organic silicon emulsion, wax emulsion, wollastonite powder, mica powder and additives to improve the hiding power and hardness of the coating. The present invention limits the amount of nano-modified titanium-silicon-aluminum powder to the above range, which can further improve the hardness of the coating.
[0038] The present invention has no special limitation on the source of the nano-modified titanium-silicon-aluminum powder, and commercial products known to those skilled in the art can be used. In an embodiment of the present invention, the nano-modified titanium-silicon-aluminum powder is nano-modified titanium-silicon-aluminum powder T-1, from Shaanxi Inorganic Library.
[0039] The stain-resistant high-hardness coating provided by the present invention includes 3 to 30% heavy calcium carbonate by mass percentage. In an embodiment of the present invention, the heavy calcium carbonate may be specifically 5%, 10%, 15%, 20%, 25% or 30%. The addition of heavy calcium carbonate in the present invention can improve the hiding power and durability of the coating, while improving the stability and thixotropy of the coating. The present invention limits the amount of heavy calcium carbonate to the above range, which can further improve the various properties of the coating.
[0040] The present invention has no particular limitation on the source of the heavy calcium carbonate, and commercially available products known to those skilled in the art may be used.
[0041] The stain-resistant high-hardness coating provided by the present invention comprises 2-10% wollastonite powder, preferably 5-10% by mass percentage. In the present invention, the wollastonite powder cooperates with nano-modified titanium-silicon-aluminum powder, mica powder, emulsion, and additives to improve the hiding power and hardness of the coating. The present invention limits the amount of wollastonite powder to the above range, which can further improve the hardness of the coating.
[0042] The present invention has no particular limitation on the source of the wollastonite powder, and commercially available products known to those skilled in the art may be used.
[0043] The stain-resistant high-hardness coating provided by the present invention comprises 0.5-3%, preferably 1-3%, and more preferably 1.5-3% of mica powder by mass percentage. In the present invention, the mica powder cooperates with nano-modified titanium-silicon-aluminum powder, wollastonite powder, emulsion, and additives to improve the hiding power and hardness of the coating. The present invention limits the amount of mica powder to the above range, which can further improve the hardness of the coating.
[0044] The present invention has no particular limitation on the source of the mica powder, and commercially available products known to those skilled in the art may be used.
[0045] The stain-resistant high-hardness coating provided by the present invention comprises 0.2-2.5% of nano titanium phosphate, preferably 0.5-2.5%, and more preferably 1-2.5%, by mass percentage. In the present invention, the nano titanium phosphate, diatomaceous earth, and mica powder work together to decompose harmful substances such as formaldehyde adsorbed by the coating, purify indoor toxic air, and eliminate harm to the human body. The present invention limits the amount of nano titanium phosphate to the above range, which can further improve the decomposition of harmful substances such as formaldehyde by the coating.
[0046] The present invention has no particular limitation on the source of the nano-titanium phosphate, and commercially available products known to those skilled in the art may be used.
[0047] The stain-resistant high-hardness coating provided by the present invention comprises 1-5% diatomaceous earth, preferably 2-5% by mass percentage. In the present invention, the diatomaceous earth, nano-titanium phosphate and mica powder work together to decompose harmful substances such as formaldehyde adsorbed by the coating, purify indoor toxic air, and eliminate harm to the human body. The present invention limits the amount of diatomaceous earth to the above range, which can further improve the decomposition of harmful substances such as formaldehyde by the coating.
[0048] The present invention has no particular limitation on the source of the diatomaceous earth, and commercially available products known to those skilled in the art may be used.
[0049] The stain-resistant high-hardness coating provided by the present invention includes 0.2-2%, preferably 0.5-2%, and more preferably 1-2% of the negative ion additive by mass percentage. In the present invention, the negative ion additive can continuously release negative oxygen ions, providing health care effects such as stabilizing the spirit, promoting metabolism and blood circulation, relieving fatigue, and maintaining health for the human body. The present invention limits the amount of the negative ion additive to the above range, which can further increase the amount of negative oxygen ions released by the coating.
[0050] In the present invention, the negative ion additive preferably includes at least one of tourmaline, ice stone and medical stone.
[0051] The present invention has no particular limitation on the source of the anion additive, and commercially available products known to those skilled in the art may be used.
[0052] The stain-resistant high-hardness coating provided by the present invention includes 0.1-0.85% of the anti-scratch additive, preferably 0.3-0.85%, and more preferably 0.5-0.85%, by mass percentage. The present invention limits the amount of the anti-scratch additive to the above range, which can further improve the anti-scratch performance of the coating.
[0053] The present invention has no special limitation on the source of the anti-scratch agent, and a commercial product known to those skilled in the art can be used. In an embodiment of the present invention, the anti-scratch agent is anti-scratch agent 3556, a new material from Cima.
[0054] The stain-resistant high-hardness coating provided by the present invention comprises 20-50% of silicone emulsion, preferably 30-50% by mass percentage. In the present invention, the silicone emulsion and the wax emulsion are compounded so that the coating has super stain resistance and graffiti resistance, and a very high stain removal rate. The present invention limits the amount of silicone emulsion to the above range, which can further improve the stain resistance of the coating.
[0055] In the present invention, the solid content of the silicone emulsion is preferably 40-50%, more preferably 45-50%, and further preferably 47%.
[0056] The present invention has no special limitation on the source of the organosilicon emulsion, and a commercial product known to those skilled in the art can be used. In an embodiment of the present invention, the organosilicon emulsion is RS-996AD, Bardeful.
[0057] The stain-resistant high-hardness coating provided by the present invention comprises 0.2-2%, preferably 0.5-2%, and more preferably 1-2% of the wax emulsion by mass percentage. In the present invention, the wax emulsion and the organosilicon emulsion are compounded so that the coating has super stain resistance and graffiti resistance, and a very high stain removal rate. The present invention limits the amount of the wax emulsion to the above range, which can further improve the stain resistance of the coating.
[0058] In the present invention, the solid content of the wax emulsion is preferably 30-40%, more preferably 35-38%, and further preferably 36%.
[0059] The present invention has no particular limitation on the source of the wax emulsion, and commercial products known to those skilled in the art can be used. In an embodiment of the present invention, the wax emulsion comes from Shandong Zhongkang Guo Innovation Materials.
[0060] The stain-resistant high-hardness coating provided by the present invention includes 0.1-1%, preferably 0.2-1%, of the preservative in terms of mass percentage. The present invention limits the amount of the preservative to the above range, which can improve the anti-corrosion performance of the coating.
[0061] The present invention has no particular limitation on the source of the preservative, and commercial products known to those skilled in the art can be used. In an embodiment of the present invention, the preservative is Xinke-DIM, a broad-spectrum preservative, Nantong Boda.
[0062] The stain-resistant high-hardness coating provided by the present invention includes 0.5-4%, preferably 1-4%, and more preferably 2-4% of a film-forming aid in terms of mass percentage. The present invention limits the amount of the film-forming aid to the above range, which can further improve the film-forming property of the coating.
[0063] In the present invention, the film-forming aid preferably includes at least one of OE300 and TEXANOL. The present invention has no special limitation on the source of the film-forming aid, and commercial products known to those skilled in the art can be used. In an embodiment of the present invention, the film-forming aid is OE300 odorless film-forming aid or TEXANOL fatty alcohol, Qilu Eastman.
[0064] The stain-resistant high-hardness coating provided by the present invention includes 0.1-1%, preferably 0.2-1%, of a leveling agent by mass percentage. The present invention limits the amount of the leveling agent to the above range, which can further improve the leveling property of the coating, ensure the flatness and uniformity of the coating film, and avoid defects such as shrinkage cavities.
[0065] The present invention has no special limitation on the source of the leveling agent, and a commercial product known to those skilled in the art can be used. In an embodiment of the present invention, the leveling agent is RM-2020, polyurethane, Dow, USA.
[0066] The stain-resistant high-hardness coating provided by the present invention includes 0.1-1%, preferably 0.5-1%, of a thickener by weight percentage. The present invention limits the amount of the thickener to the above range, which can make the coating have a suitable viscosity, improve the stability of the coating, facilitate construction, and improve the quality of the coating.
[0067] The present invention has no particular limitation on the source of the thickener, and a commercial product known to those skilled in the art can be used. In an embodiment of the present invention, the thickener is TT-935, an associative acrylic acid, manufactured by Dow Chemical, USA.
[0068] Calculated by mass percentage, the stain-resistant high-hardness coating provided by the present invention includes a balance of water.
[0069] Nano-modified titanium-silicon-aluminum powder is added to the coating of the present invention to improve the hiding power and hardness of the coating; organic silicon emulsion and wax emulsion are compounded to make the coating have super strong stain resistance and graffiti resistance, and extremely high stain removal rate; the composition of the coating and the amount of each component are controlled so that the coating can also continuously release negative oxygen ions, absorb formaldehyde, and purify the air, while the VOC content is low.
[0070] In the present invention, the preparation method of the stain-resistant high-hardness coating preferably comprises the following steps:
[0071] (1) mixing part of water, nano-modified titanium-silicon-aluminum powder, a dispersant, a wetting agent, hydroxyethyl cellulose, part of a defoaming agent, a pH regulator and a film-forming aid to obtain a mixed solution;
[0072] (2) mixing the mixed solution obtained in step (1) with titanium dioxide, heavy calcium carbonate, wollastonite powder, nano titanium phosphate, mica powder, diatomaceous earth and a negative ion additive to obtain a mixed slurry;
[0073] (3) The mixed slurry obtained in step (2) is mixed with silicone emulsion, wax emulsion, preservative, remaining defoamer, anti-scratch aid, film-forming aid, thickener, leveling agent and remaining water to obtain a stain-resistant high-hardness coating.
[0074] In the present invention, part of water, nano-modified titanium-silicon-aluminum powder, a dispersant, a wetting agent, hydroxyethyl cellulose, part of a defoamer, a pH regulator and a film-forming aid are preferably mixed to obtain a mixed solution.
[0075] In the present invention, the mass of the partial water is preferably 70-80% of the total water mass.
[0076] In the present invention, the mass of the partial defoamer is preferably 30 to 50% of the mass of the total defoamer.
[0077] In the present invention, the mixing of part of the water, nano-modified titanium-silica-aluminum powder, dispersant, wetting agent, hydroxyethyl cellulose, part of the defoamer, pH regulator and film-forming aid is preferably as follows: nano-modified titanium-silica-aluminum powder is added to part of the water, dispersed at a speed of 800-1000 rpm for 10-15 minutes, and then the dispersant and wetting agent are added in sequence, and then hydroxyethyl cellulose is slowly added at a speed of 700-900 rpm, and after it is completely dissolved, part of the defoamer, pH regulator and film-forming aid are added in sequence.
[0078] The invention has no particular limitation on the adding rate of the slowly adding hydroxyethyl cellulose, which is relatively slow to ensure that the hydroxyethyl cellulose does not agglomerate during the adding process and is fully dispersed. The invention can make the hydroxyethyl cellulose fully dispersed by slowly adding the hydroxyethyl cellulose.
[0079] After obtaining the mixed solution, the present invention preferably mixes the mixed solution with titanium dioxide, heavy calcium carbonate, wollastonite powder, nano titanium phosphate, mica powder, diatomaceous earth and a negative ion additive to obtain a mixed slurry.
[0080] In the present invention, the mixing is preferably grinding; the grinding rate is preferably 1200-1600 rpm; and the grinding time is preferably 40-50 min.
[0081] In the present invention, the fineness of the mixed slurry is preferably 35 to 40 μm.
[0082] After obtaining the mixed slurry, the present invention preferably mixes the mixed slurry with silicone emulsion, wax emulsion, preservative, remaining defoamer, anti-scratch aid, film-forming aid, thickener, leveling agent and remaining water to obtain a stain-resistant and high-hardness coating.
[0083] In the present invention, the mixing of the mixed slurry with the silicone emulsion, wax emulsion, preservative, remaining defoamer, anti-scratch aid, film-forming aid, thickener, leveling agent and remaining water is preferably as follows: at a rotation speed of 700 to 900 rpm, the silicone emulsion, wax emulsion, preservative, remaining defoamer, anti-scratch aid and film-forming aid are sequentially added to the mixed slurry, dispersed for 20 to 40 minutes, and then the thickener, leveling agent and remaining water are sequentially added, dispersed for 5 to 10 minutes, and then stirred at a rotation speed of 500 to 700 rpm for 1 to 10 minutes to drive out bubbles.
[0084] After the mixing is completed, the present invention preferably filters the mixture obtained by mixing to obtain a stain-resistant and high-hardness coating.
[0085] The present invention has no special limitation on the filtering operation, and any filtering technical solution well known to those skilled in the art may be used.
[0086] The preparation method of the present invention can make the components mixed more fully.
[0087] The present invention also provides the use of the stain-resistant high-hardness coating described in the above technical solution in interior walls.
[0088] The present invention has no special limitation on the application operation, and the technical solution for applying the coating on the interior wall which is well known to those skilled in the art can be adopted.
[0089] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0090] Example 1
[0091] The composition of the stain-resistant high-hardness coating in Example 1 and the amount of each component are shown in Table 1;
[0092] The preparation method of the stain-resistant high-hardness coating is:
[0093] (1) Adding nano-modified titanium-silicon-aluminum powder to a portion of water (80% of the total water mass), dispersing at a speed of 900 rpm for 15 min, then adding a dispersant and a wetting agent in sequence, and then slowly adding hydroxyethyl cellulose at a speed of 800 rpm. After the hydroxyethyl cellulose is completely dissolved, adding a portion of the defoamer (40% of the total defoamer mass), a pH regulator and a film-forming aid in sequence to obtain a mixed solution;
[0094] (2) grinding and mixing the mixed solution obtained in step (1) with titanium dioxide, heavy calcium carbonate, wollastonite powder, nano titanium phosphate, mica powder, diatomaceous earth and a negative ion additive at a speed of 1500 rpm for 45 minutes to obtain a mixed slurry with a fineness of 35 to 40 μm;
[0095] (3) At a rotation speed of 800 rpm, silicone emulsion, wax emulsion, preservative, remaining defoaming agent, anti-scratch aid and film-forming aid are added to the mixed slurry obtained in step (2) in sequence, and dispersed for 30 minutes. Then, thickener, leveling agent and remaining water are added in sequence, dispersed for 5 minutes, and then stirred at a rotation speed of 600 rpm for 5 minutes to remove bubbles, filtered, and a stain-resistant high-hardness coating is obtained.
[0096] The hardness of the coating in Example 1 was tested using a pencil hardness test method, and the hardness was 2H.
[0097] Comparative Examples 1-2
[0098] The composition of the coatings and the amounts of the components in Comparative Examples 1 to 2 are shown in Table 1;
[0099] The preparation method is the same as that of Example 1.
[0100] Table 1 Composition of coatings and dosage of each component in Example 1 and Comparative Examples 1-2
[0101]
[0102]
[0103] The paint in Example 1 was tested according to the standard of "Synthetic Resin Emulsion Interior Wall Paint" (GB / T 9756-2018), and the test results are shown in Table 2.
[0104] Table 2 Test results of coating in Example 1
[0105]
[0106]
[0107] It can be seen from Table 2 that the coating provided by the present invention belongs to the superior grade.
[0108] The coating in Example 1 was tested according to the standard of "Technical Requirements for Environmental Labeling Products - Water-Based Coatings" (HJ 2537-2014), and the test results are shown in Table 3.
[0109] Table 3 Test results of coating in Example 1
[0110] project Test results Volatile Organic Compounds (VOCs) 33g / L Free formaldehyde mg / Kg Not detected BTEX mg / Kg Not detected Soluble lead mg / Kg Not detected Soluble chromium mg / Kg Not detected Soluble cadmium mg / Kg Not detected Soluble mercury mg / Kg Not detected
[0111] It can be seen from Table 3 that the coating provided by the present invention fully meets the technical requirements of environmental labeling water-based coating products.
[0112] The coating in Example 1 was tested according to the standard of "Purification Performance of Indoor Air Purification Functional Coating Materials" (JC / T1074-2021), and the test result of formaldehyde purification efficiency was as high as 89.6%, and the test result of formaldehyde purification effect durability was as high as 79.1%, which meets the requirements of "Class 1 Materials" in the standard of "Purification Performance of Indoor Air Purification Functional Coating Materials" (JC / T 1074-2021).
[0113] The coating in Example 1 was tested for the amount of negative ions induced by air according to the method provided in the standard "Negative Ion Functional Coatings" (HG / T4109-2009), and the result was 2605 / (s·cm 2), and its radioactivity limit fully complies with the requirements of Class A decoration materials in the "Limits of Radioactive Nuclides in Building Materials" (GB 6566-2010), and its scope of use is not restricted.
[0114] The coating in Example 1 was tested according to the "Test method for stain resistance of interior wall paint coatings" in the "Test method for stain resistance of architectural paint coatings" (GB / T 9780-2013). The coating had a removal ability of 10 for six types of stains, namely, edible vinegar, black tea, blue-black ink, water-soluble melanin, alcohol-soluble melanin, vaseline, and carbon black mixture (1.5 g of carbon black, 20 g of kaolin, and 1000 mL of water), which represents the highest stain removal rate, indicating that most stains can be removed.
[0115] In summary, the coating provided by the present invention has high hardness and excellent stain resistance.
[0116] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A stain-resistant high-hardness coating, comprising the following components by mass percentage: 0.4-1.5% dispersant, 0.02-0.5% wetting agent, 0.1-0.55% hydroxyethyl cellulose, 0.1-0.5% defoaming agent, 0.02-0.4% pH value regulator, 0.2-3% film-forming aid, 5-30% titanium dioxide, 0.2-2% nano-modified titanium silicon aluminum powder, 3-3% heavy calcium carbonate 0%, wollastonite powder 2-10%, mica powder 0.5-3%, nano titanium phosphate 0.2-2.5%, diatomaceous earth 1-5%, negative ion additive 0.2-2%, anti-scratch agent 0.1-0.85%, silicone emulsion 20-50%, wax emulsion 0.2-2%, preservative 0.1-1%, film-forming agent 0.5-4%, leveling agent 0.1-1%, thickener 0.1-1% and the balance water.
2. The stain-resistant high-hardness coating according to claim 1, characterized in that: The dispersants include sodium salt dispersants and ammonium salt dispersants.
3. The stain-resistant high-hardness coating according to claim 2, characterized in that: The mass ratio of the sodium salt dispersant to the ammonium salt dispersant is (0.4-5):
1.
4. The stain-resistant high-hardness coating according to claim 1, characterized in that: The pH value regulator includes at least one of organic ammonia and AMP-95; the pH value of the stain-resistant high-hardness coating is 8-9.
5. The stain-resistant high-hardness coating according to claim 1, characterized in that: The film-forming aid comprises at least one of propylene glycol, ethylene glycol and ethylene glycol butyl ether.
6. The stain-resistant high-hardness coating according to claim 1, characterized in that: The titanium dioxide is rutile titanium dioxide.
7. The stain-resistant high-hardness coating according to claim 1, characterized in that: The negative ion additive includes at least one of tourmaline, ice stone and medical stone.
8. The stain-resistant high-hardness coating according to claim 1, characterized in that: The film-forming aid includes at least one of OE300 and TEXANOL.
9. The stain-resistant high-hardness coating according to claim 1, characterized in that: The defoamer comprises at least one of a mineral oil defoamer, a silicone defoamer and a non-silicon defoamer.
10. Use of the stain-resistant and high-hardness coating according to any one of claims 1 to 9 in interior walls.
Citation Information
Patent Citations
Method for inorganic, organic modified surface of white titanium pigment
CN101003693A
Stain-resistant white emulsion paint and preparation method thereof
CN105219199A
Total effect integrated internal wall coating material and preparation method thereof
CN106883752A